PERANCANGAN DAN PROTOTYPING MULTIMEDIA PEMBELAJARAN ALGORITMA DAN DASAR PEMROGRAMAN - hendri raharjo (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2012)
Creativity-based independent study students is done through the computer to encourage students todo the analysis and improvement of knowledge, explore, exploit and manage information, and generate information and knowledge itself. Students can make the exploration of knowledgeindependently. Learning materials developed through the model vary from the very day CBLintroduction of the computer, interacting with the computer, the use of specific software (wordprocessors, spreadsheets, or databases) and the creation of learning programs through aprogramming language. Conventional education system is in progress at this time start to have problems in relation to theneeds of 21st century education. Learning still tend in the direction of the pattern, where moredominate role of the learning process. Students tend to be regarded as an object with the samepotential so that plurality is not a part of the students in the learning process. The objective of the research development of this learning module is a learning algorithm basedmultimedia and programming that helps the learning process in the academic environment,enabling students to accelerate the understanding of the teaching materials, especially algorithms and programming and to give freedom to students to make learning an explorative and repetitive at- discussion of each subject so that teaching materials for possible use by students with learning thevarious characters. Model development system using the method of prototyping are approaches to softwaredevelopment approach using a model of instructional design / development with the approachfollowed by the model system. model generally recommend this approach, the sequence of activitythat includes analysis, design, development, implementation, and evaluation (ADDIE)Keywords: Computer based learning (CBL), learning, algorithms and programming, multimedia